Risk Factors of Abortion Cases Admitted at Selected Tertiary Level Public Hospitals in Dhaka District (International Journal of Nursing Research in Midwifery, Obstetrics and Gynecology, 2026)
Abortion has become a growing concern in Bangladesh because it results in women’s health at risk. However, the health professionals or nurses providing health education related to pregnancy and abortion laws, can reduce the risks if they become aware about the risk factors of abortion cases. The present study is a descriptive type of cross-sectional study which was carried out among 158 purposively selected abortion patients admitted at Combined Military Hospital, Dhaka from July 2022 to February 2023 with the aim to find out the risk factors of abortion cases. Data were collected by administering a written semi-structured questionnaire. Out of total 158 respondents, majority [120(75.9%)] belongs to 21-30years of age group. The study shows that most of the respondents [66(41.8%)] had degree and above level of education and 45.6% had monthly family incomes 16000-25000 Taka. In this study [44(27.8%)] respondents used contraceptives and maximum used oral contraceptives pill [46(29.10%)]. It is evident from the study that maximum [108(68.4%)] of the respondents had age at marriage 16-20 and largest respondents [138(87.3%)] had no history of trauma during pregnancy, majority [84(53.2%)] had no history of previous abortion. Based on the present study, it shows that most of the respondents [132(83.5%)] had spontaneous abortion. Maximum respondents [100(63.3%)] didn’t know the actual causes of abortion. Among the respondents only [40(25.3%)] had history of MR. Maximum respondents were free from disease during pregnancy. For this purpose, this study indicates that the topic is a big maternal health issue. All these findings suggest that patients are apparently aware about risk factors of abortion but some of the respondents were not aware which needs appropriate measure for increasing awareness to reduce the incidence of abortion. So further in-depth studies should be conducted in this regard. Study on larger sample size is necessary for more accurate findings.
Keywords: abortion; health education; nurses; pregnant women; risk factors; trauma